(untitled) (Bangladesh Journal of Botany, 2013)
Dynamics of phytoplankton primary productivity were determined in a eutrophic water body of Dhaka Metropolis fortnightly for one year. The mean value of daily rate of primary productivity was 10.05 gC/m2/d and annual sum of primary productivity was estimated 3669.5 gC/m2/y. The yearly mean value of conductivity, pH, alkalinity, SRP and SRS were 486.66 ?S/cm, 7.21, 4.02 meq/l, 0.75 mg/l and 49.75 mg/l, respectively which indicated the intensity of contamination from the catchment. Significant correlations were obtained among the variables (day length, irradiance, water temperature and DO) relating to primary productivity. Green soup like algal bloom was found to occur on most occasions. The productivity was confined to the upper few centimeter depth of the water indicating a typical eutrophic nature of the water body. DOI: http://dx.doi.org/10.3329/bjb.v41i2.13437 Bangladesh J. Bot. 41(2): 135-142, 2012 (December)